Determining optimal outcome measures in a trial investigating no routine gastric residual volume measurement in critically ill children - Tume,L; Arch,B; Woolfall,K; Roper,L; Deja,E; Jones,A; Latten,L; Eccleston,H; Nazima,P; Preston,J; Beissel,A; Andrzejewska,I; et al. (Journal of Parenteral and Enteral Nutrition, 2021)
BackgroundChoosing trial outcome measures is important. When outcomes are not clinically relevant or important to parents/patients, trial evidence is less likely to be implemented into practice. This study aimed to determine optimal outcome measures for a trial of no routine gastric residual volume (GRV) measurement in critically ill children.MethodsA mixedmethods approach was used: a focused literature review, parent and clinician interviews, a modified 2round Delphi, and a stakeholder consensus meeting.ResultsThe review generated 13 outcomes. Fourteen pediatric intensive care unit (PICU) parents proposed 3 additional outcomes; these 16 were then rated by 28 clinicians in Delphi round 1. Six further outcomes were proposed, and 22 outcomes were rated in the second round. No items were voted “consensus out.” The 18 “noconsensus” items were voted in a facetoface meeting by 30 participants. The final 12 outcome measures were time to reach energy targets, ventilatorassociated pneumonia, vomiting, time enteral feeds withheld per 24 hours, necrotizing enterocolitis, length of invasive ventilation, PICU length of stay, mortality, change in weight and markers of feed intolerance (parenteral nutrition administered), feed formula altered, and change to postpyloric feeds all secondary to feed intolerance.ConclusionWe have identified 12 outcomes for a trial of no GRV measurement through a multistage process, seeking views of parents and clinicians.